Bibliometric Mapping of School Garden Studies: A Thematic Trends Analysis - Castillo-Guajardo, D (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
This paper analyzes the thematic trends in school garden studies over the past few decades, using a relational bibliometric methodology on a corpus of 392 articles and review articles indexed in the Web of Science Core Collection. The paper seeks to understand how researchers have studied the concept over the last few decades in various disciplines, spanning approximately eighty Web of Science categories. The results show that there is a critical mass of scientific research studying school gardens. The analysis shows the thematic trends in discussion journals, discussion terminology, and consolidates classic papers and some novel authors and papers. The studies and their theoretical trends lead to refocusing the analysis on the effects of school gardens beyond the educational, thanks to the contribution of authors from more than fifty countries engaged in the study of these activities. This work constitutes new challenges for this line of research, raising interdisciplinary research challenges between horticultural, environmental, technological, educational, social, food, nutritional, and health sciences. © 2023 by the authors.